Penerapan Pembelajaran Berdiferensiasi Dalam Upaya Meningkatkan Hasil Belajar Matematika Pada Materi Analisis Regresi Linear Sederhana Kelas XI TITL (Teknik Instalasi Tenaga Listrik) 2 SMK N 5 Surabaya Tahun Ajaran 2023/2024 - Nur Layli Indah Puspita; Fatkul Anam; Arif Santoso (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
The research was conducted based on the problem of students in class XI TITL 2 SMK N 5 Surabaya This research aims to improve student learning outcomes by using differentiated learning based on student learning styles with differentiated content aspects. This research uses the PTK (Classroom Action Research) method with a quantitative approach and data collection techniques using diagnostic assessments (prestest) and summative assessments (posttest). The results of research using differentiated learning based on students' learning styles with differentiated content aspects show that there is an increase in learning outcomes which can be seen from pre-cycle activities with the percentage of learning completeness increasing from 18% to 43% in cycle I, then increasing to 78% in cycle II. From these results it can be concluded that research using differentiated learning based on students' learning styles based on differentiated content aspects has succeeded in improving the learning outcomes of class XI TITL 2 SMK N 5 Surabaya in mathematics lessons simple linear regression analysis material.